The Influence of Competencies and Career Development on Employee Retention with Organizational Commitment as Variable Intervention (Case Study on Penderes Employees PTPN. IV Regional 1 Kebun Sarang Giting) - Sari Nurulita Arafah; Emi Wakhyuni; Yohny Anwar (Yayasan Multidimensi Kreatif, 2024)
This study examines the role of competence, career development, and organizational commitment as factors influencing employee retention at PT Perkebunan Nusantara IV (Persero), a State-Owned Enterprise (BUMN) in Indonesia engaged in the management and processing of plantation products. The research addresses the significance of human resources in achieving company goals, emphasizing the need for effective employee retention strategies to prevent turnover and ensure organizational success. The study highlights how competence, as defined by Spencer and Spencer (1993), and career development are crucial in retaining employees. Organizational commitment, encompassing normative, affective, and continuous commitment, is explored as a mediating variable that may clarify the relationship between competence and employee retention. The findings suggest that higher levels of competence and perceived organizational support positively influence organizational commitment, which in turn enhances employee retention. This study contributes to the literature by offering insights into the mediating role of organizational commitment, providing a unique perspective on how companies can improve retention rates by fostering employee competence and career development.